Comparison of anterior cervical discectomy and fusion with the zero-profile device versus plate and cage in treating cervical degenerative disc disease: A meta-analysis. (November 2016) - Duan, Yuchen; Yang, Yunbei; Wang, Yayi; Liu, Hao; Hong, Ying; Gong, Quan; Song, Yueming
Highlights: Zero-p implantation appears to be a safe and effective procedure. Zero-p implantation has reduced incidence of dysphagia and increased subsidence rate compared to plate and cage. The superiority of plate and cage is evident in the restoration of cervical lordosis of multilevel surgery. Zero-p implantation and the plate and cage both have respective advantages and disadvantages. Abstract: Z ero-profile device was applied to diminish the irritation of the esophagus in the treatment of cervical degenerative disc disease. However, the clinical application of the zero-profile device has not been testified with clinical evidence. The aim of the meta-analysis was to systematically compare the safety and effectiveness of anterior cervical discectomy and fusion with zero-profile device with plate and cage for the treatment of cervical degenerative disc disease. Electronic searches of PubMed and Embase were conducted up to May 2015. Relevant studies were included. Weighted mean difference (WMD) and 95% confidence intervals (CI) were assessed for continuous data. Risk ratio (RR) and 95% CI were assessed for dichotomous data. P value <0.05 was considered to be significant. Eleven studies were included in the meta-analysis. Compared with plate and cage, zero-p is associated with lower operation time of two-level surgery, less intraoperative blood loss, higher subsidence rate, higher JOA score, lower incidence of dysphagia in short-term (RR: 0.72, 95% CI [0.58, 0.90], P = 0.005, I 2 = 22%) and long-term (RR: 0.12, 95% CI [0.05, 0.30], P < 0.00001, I 2 = 0%) and lower Cobb angle of multilevel surgery (WMD: −3.16, 95% CI: [−4.35, −1.97], P < 0.00001, I 2 = 0%). No significant difference was found in one-level and two-level Cobb angle, fusion rate and operation time of one-level and three-level surgery. Both zero-p implantation and the plate and cage have respective advantages and disadvantages.